UKRAINIAN SCHOLARS ON GUARD OF MOTHER WORD - Lesiuk, M. P. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
The article deals with the discrimination of the Ukrainian language, its chauvinistic oppression on the part of the colonial Russian-Soviet regime and highlighting this problem in the works of Ukrainian linguists.